An Decadial Empirical Overview on Contributions of India’s Tourism Towards Employment and Gross Domestic Product: tourism and economy - N.S, Vijayalakshmi (Turizam, 2025)
The economy evolves around a vital macro-economic indicator the gross domestic product, which gives us vivid picture of the state of evolvement of the economy in producing the final value of goods and services. The related activities associated with tourism like art, recreation and entertainment have been pioneer to establishing employment even to the vulnerable sections of the society. These on and off employment sources have to churn to be long term sources of income for a long standing direct and indirect contribution to gross domestic product.